PENINGKATAN PEMAHAMAN DAN KESADARAN AKAN SANITASI DIRI BAGI WARGA LINGKUNGAN HIERONIMUS I - Marvel Guntur Wijanarko; Antonius Jimmy Widagdo; Ellen Gracia Hindrawan; Jenifer Tifany Kustiawan; Sandy Budi Hartono; Aning Ayucitra; Shella P. Santoso; Maria Yuliana (LPPM, Universitas Katolik Widya Mandala Surabaya, 2022)
Various types of diseases can be prevented through a very simple approach, namely improving personal hygiene. Understanding and awareness of the importance of maintaining personal sanitation needs to be continuously improved. Increased awareness of self-sanitation and the ability of community members to prevent various types of diseases will increase if the community also has the knowledge and ability to produce products to maintain personal sanitation. To achieve this goal, counseling and training were held for residents of the Hieronimus I regarding personal sanitation and also how to produce products that can be useful in supporting personal hygiene, namely hand sanitizer